Correlation Between Cognition and Balance Among Middle-Aged and Older Adults Observed Through a Tai Chi Intervention Program - Xiao, Tao; Yang, Lin; Smith, Lee; Loprinzi, Paul D.; Veronese, Nicola; Yao, Jie; Zhang, Zonghao; Yu, Jane Jie (Frontiers in Psychology, 2020)
Background: Age-associated decline in cognition and balance may cause severe ability loss for daily living activities among middle-aged and older adults. The relationship between cognition and balance in this aging population remains to be explored. Objective: The present study is exploratory in nature and aimed to examine the relationship between balance (both static and dynamic components) and global cognitive function among middle-aged and older adults through TC practice as a research avenue. . Methods: A short-term (12 weeks) intervention of TC was conducted among middle-aged and older adults in the community setting. Global cognitive function (using the Chinese version of the Montreal Cognitive Assessment score (MoCA) and balance (i.e., one leg standing test score; Timed Up and Go Test score, TUGT) of all participants were assessed before and after the intervention. Age, body mass index (BMI), sex, and physical fitness variables (Chair Stand Test, CST; the 6-Meter Walk Test, 6MWT) were also collected as confounding factors. Results: Significant moderator effects of baseline BMI (p = 0.048) and baseline CST (p = 0.026) on the association between the averaged baseline leg balance score and the dichotomized baseline MoCA score were found. A potential association between observed change scores of balance and cognitive function was also evident. Conclusion: Cognitive function and balance are interrelated in middle-aged and older adults. The association with global cognitive function is more robust for static balance when compared to dynamic balance, and such association is moderated by BMI and strength of lower limbs. Future research is warranted to further confirm the cause-effect relationship of cognitive function and balance and its influencing factors among middle-aged and older adults in intervention studies using randomized controlled trials.